A Path Model of Innovative Customer Orientation and Company Performance with the Moderating Influence of Company Training - Demirel, Ayşe Gonül; Yayla, Neslihan (International Review of Management and Marketing, 2022)
This study used a sample of salespeople at various companies to substantiate a path model of innovativeness, customer orientation, and performance; thus, it offers a multi-disciplinary framework. Results indicated a moderating influence of company training programs on the relationship between customer orientation and performance, which can have several implications for human resource managers and sales contact employees. Two features, testing the influence of training activities and measuring customer orientation from the employees' perceptions, distinguish this study from previous studies.